Criopreservação de sêmen de galos - Laan, Guilherme Martino Van Der (2007)
Adding extenders to poultry semen is currently used in artificial insemination programs to optimize the management of genetically superior males. Fresh semen fertility usually declines after 1 hour of collection, raising the need to use diluents and low temperatures to store semen for longer periods. Low density lipoprotein (LDL), extracted from the egg yolk, is used as a component of various mammalian semen diluents, however its application on poultry semen has not been evaluated. Regarding cryopreservation, different methodologies have been developed during the past years. One alternative is to use dimethylacetamide (DMA) as a cryoprotectant. The best results with DMA are obtained when semen is subjected to ultra-fast freezing, in pellets, and to a fast thawing at 60ºC. The objective of this work was to establish protocols to preserve rooster sperm, focusing on the use of LDL as a component of the refrigeration diluent, and on DMA as a internal cryoprotectant for freezing. To reach these objectives, the effect of adding different levels of LDL liposomes to the cooling diluent, upon the quality characteristics of semen refrigerated at 5 °C, was evaluated. The quality of semen frozen with DMA, packed in straws or pellets, and thawed in three different temperatures was also evaluated. The results obtained allow to conclude that: adding 6% of LDL liposomes to the cooling diluent preserves the general sperm quality, suggesting that improvements on fertility could be obtained if a limit in lipoprotein supplementation is imposed; body temperature (40°C) is most suitable for thawing sperm frozem with DMA; and packing sperm in straws is more efficient than packing in pellets. This last observation is of great value, since storing semen in straws is more appropriate due to sanitary reasons, and more convenient for ejaculates identification, especially for field application of genetic banks.